(untitled) (Medico Legal Update, 2021)
Background: Diabetes is a complex, chronic illness requiring continuous medical care with multi-factorial risk-reduction strategies beyond glycemic control. Ongoing diabetes self-management education and support are critical to preventing acute complications and reducing the risk of long term complications(1). Diabetes mellitus occurs when there are raised levels of glucose in aperson’s blood because their body cannot produceany or enough of the hormone insulin, or cannot effectively use the insulin it produces. The causes of type 2 diabetes are not completely understood but there is a strong link with overweight and obesity, and increasing age, as well as with ethnicity and family history.Aim: This study intended to assess and study correlation between serum levels of leptin and thyroid hormones in diabetic and obese patients.Subject and Method:a case control study was conducted at the center of diabetes management and research between 1st of December 2019 to the 15th of May 2020. A fasting blood sample was taken from all participants for measurement of biochemical parameters. The information regarding the problem and demographic characteristics was obtained directly from the participants by interviewing them, using a prepared questionnaire. The weight and the height were using a medical scale machine. The body mass index was calculated according to its equation.Results: Results of the present study show that leptin hormone was significantly high in serum of type 2 diabetic patients group compared with overweight and obese group (P < 0.000). A significant positive correlation with serum leptin and body mass index. Results also show that TSH hormone (P < 0.01), and FBS were significantly high(P < 0.000), while T3 and T4 decrease significant (P < 0.05) in type 2 diabetic patients groupand compared with control groups.